More than de minimis: FAPE in the Post Endrew F. Era. Issue 1 (January 2021) - McKenna, John William; Brigham, Frederick J.
Federal regulations for special education services have focused primarily on procedural issues since the Rowley decision, which held that Individualized Education Programs (IEPs) need only be reasonably calculated to yield educational benefit. However, the minimum threshold for benefit has changed with the recent Endrew F. decision as IEPs must yield more than de minimis progress. To ensure sufficient progress toward the achievement of ambitious goals, schools must develop IEPs that meet procedural and substantive requirements, employ interventions with clear evidence of effectiveness, effectively measure student response to services, and to communicate this information with parents/guardians so that they can actively participate in this process. Manuscripts invited for this special issue include investigations of IEP quality; co-teaching; intervention studies in reading, writing, and mathematics; meta-analytic findings regarding social studies education; and a discussion of the implications of Endrew F. for different student disability populations. These papers discuss challenges faced by stakeholders with vested interests in students with disabilities as well as areas of continued development and refinement in evidence-based practice.